2019
DOI: 10.1111/wrr.12719
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish fin regeneration involves transient serotonin synthesis

Abstract: The zebrafish is a vertebrate organism capable of regenerating many of its organs. Notably, it can undergo epimorphic regeneration of its fins after amputation. This process occurs through the formation of a wound epithelium and the dedifferentiation of mesenchymal and bone‐forming cells, which form a proliferative blastema. Here, we report that the entry into the regenerative process involves the local synthesis of serotonin (5‐hydroxytryptamine, 5‐HT) in the injury‐associated tissue. One day after wounding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…To test whether 5-HT is required for regeneration of HCS-cells, we applied a chemical Tph-antagonist, para-chlorophenylalanine (pcpa) (Jequier et al, 1967), which was previously validated in analytical and behavioral assays in zebrafish embryos and adults (Njagi et al, 2010; Airhart et al, 2012). Consistent with our previous study (König and Jaźwińska, 2019), we found that treatment with 5 mM pcpa, starting from 1 day before fin clipping until 3 days post-amputation, did not affect fin regeneration (Figures 15A–D). This treatment efficiently abolished 5-HT-immunoreactivity in HCS-cells, as examined on whole mount immunofluorescent stainings at 3 dpa (Figures 15A,B,E).…”
Section: Resultssupporting
confidence: 92%
“…To test whether 5-HT is required for regeneration of HCS-cells, we applied a chemical Tph-antagonist, para-chlorophenylalanine (pcpa) (Jequier et al, 1967), which was previously validated in analytical and behavioral assays in zebrafish embryos and adults (Njagi et al, 2010; Airhart et al, 2012). Consistent with our previous study (König and Jaźwińska, 2019), we found that treatment with 5 mM pcpa, starting from 1 day before fin clipping until 3 days post-amputation, did not affect fin regeneration (Figures 15A–D). This treatment efficiently abolished 5-HT-immunoreactivity in HCS-cells, as examined on whole mount immunofluorescent stainings at 3 dpa (Figures 15A,B,E).…”
Section: Resultssupporting
confidence: 92%
“…The Venn diagram was created in Venny (v2.1). 47 Multivariate statistical analyses, including principal component analysis (PCA) and heatmaps with hierarchical clustering analysis, were performed on significantly regulated proteins, 12 Platyhelminthes Rhabditophora whole body reparative stem cell zebrafish 15,16 Vertebrate Actinopterygii structure and organ reparative dedifferentiation and stem cell Xenopus/salamander 17,18 Vertebrate Amphibia structure and organ reparative dedifferentiation and stem cell lizard 19−22 Vertebrate Reptilia structure and tissue reparative dedifferentiation and stem cell African spiny mice 23−25 Vertebrate Mammalia tissue reparative dedifferentiation and stem cell deer 25−27 Vertebrate Mammalia structure physiological stem cell from DPP vs FP, and 153 from DPP vs MAP vs GC using R (v 3.5.2). 48 To conduct the PCA, R packages of "FactoMineR (v1.42)", 49 "factoextra (v1.0.5)", 50 "magrittr (v1.5)", 51 "ggpubr (v0.2.3)", 52 and "ggplot2 (v3.2.1)" 53 were used.…”
Section: Experimental Design and Statistical Rationalementioning
confidence: 99%
“…Then, SNA is converted to melatonin during the hydroxyindole-O-methyltransferase action. Serotonin is an essential chemical neurotransmitter, and its presence is of great importance in regulating mood, sleep, and appetite [ 34 , 35 ]. Melatonin is considered a vital neuromodulator, which has shown great potential as a strong antioxidant to regulate numerous body-related activities such as circadian rhythm and pain [ 36 , 37 , 38 , 39 ].…”
Section: Neurotransmitters Precursormentioning
confidence: 99%